Nilai-Nilai Pendidikan Karakter Kristiani dalam 1 Korintus 13:1-13 - Samuel Elkana (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
Believers face challenges in educating the next generation regarding forming and developing character. Character education is considered very important to be taught to believers from an early age because it is a learning process that fosters spiritual maturity in the form of Bible-based values, attitudes, and behaviors. The purpose of learning character education values is to give students a mature personality in Christ. 1 Corinthians 13:1-13 describes love with understanding and an explanation of character values. If the character is formed, it will significantly determine the nation's character in the future. This research was conducted using qualitative methods or literature presented as a biblical analysis of character education according to 1 Corinthians 13:1-13.